2016
DOI: 10.1111/jpi.12306
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reverses flow shear stress‐induced injury in bone marrow mesenchymal stem cells via activation of AMP‐activated protein kinase signaling

Abstract: Tissue-engineered heart valves (TEHVs) are a promising treatment for valvular heart disease, although their application is limited by high flow shear stress (FSS). Melatonin has a wide range of physiological functions and is currently under clinical investigation for expanded applications; moreover, extensive protective effects on the cardiovascular system have been reported. In this study, we investigated the protection conferred by melatonin supplementation against FSS-induced injury in bone marrow mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 71 publications
2
34
0
Order By: Relevance
“…Moreover, we recently demonstrated that melatonin reduced flow shear stress (FSS)-induced bone marrow mesenchymal stem cell injury by activating melatonin membrane receptors and AMPK signaling50. Kunst et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we recently demonstrated that melatonin reduced flow shear stress (FSS)-induced bone marrow mesenchymal stem cell injury by activating melatonin membrane receptors and AMPK signaling50. Kunst et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, melatonin has been reported to protect cardiomyocytes and blood vessels against fibrosis necrosis and vasculitis in radiation-induced heart disease in rats when administrated at 50 mg/kg [254]. Furthermore, melatonin was demonstrated to dose-dependently reduce flow shear stress-induced injury in bone marrow mesenchymal stem cells (BM-MSCs) through the activation of melatonin receptors and adenosine monophosphate activated protein kinase (AMPK)/ACC (acetyl-CoA carboxylase) signaling, which could benefit the patients with valvular heart disease [255]. …”
Section: Bioactivities Of Melatoninmentioning
confidence: 99%
“…Western blotting was performed as previously described [34]. Briefly, the treated hearts and cells were collected and washed with ice-cold PBS prior to the addition of lysis buffer (containing 20 mM Tris-HCl at the pH of 7.5; 150 mM NaCl; 1 mM EDTA; 1 mM EGTA; 1% Triton; 2.5 mM sodium pyrophosphate; 1 mM β-glycerophosphate; 1 mM Na 3 VO 4 ; and 1 μg/mL leupeptin).…”
Section: Western Blottingmentioning
confidence: 99%